2022
DOI: 10.1038/s41467-022-35298-y
|View full text |Cite
|
Sign up to set email alerts
|

Conserved degronome features governing quality control associated proteolysis

Abstract: The eukaryotic proteome undergoes constant surveillance by quality control systems that either sequester, refold, or eliminate aberrant proteins by ubiquitin-dependent mechanisms. Ubiquitin-conjugation necessitates the recognition of degradation determinants, termed degrons, by their cognate E3 ubiquitin-protein ligases. To learn about the distinctive properties of quality control degrons, we performed an unbiased peptidome stability screen in yeast. The search identify a large cohort of proteome-derived degro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 71 publications
4
20
0
Order By: Relevance
“…This revealed that most low abundance tiles overlapped with regions with a high-quality control degron probability (Fig. 4D ), confirming that these degrons contain the quality control degron features observed before 51 . Accordingly, when mapping the TSI onto the Parkin structure, most low-abundance tiles were found at buried positions (Supplementary Fig.…”
Section: Resultssupporting
confidence: 65%
“…This revealed that most low abundance tiles overlapped with regions with a high-quality control degron probability (Fig. 4D ), confirming that these degrons contain the quality control degron features observed before 51 . Accordingly, when mapping the TSI onto the Parkin structure, most low-abundance tiles were found at buried positions (Supplementary Fig.…”
Section: Resultssupporting
confidence: 65%
“…To distinguish key functional residues, we created a light attention model that learns these additional repressive features from large protein language models. This model improved our activity predictions and provides a valuable framework for further understanding the molecular grammar of disordered sequences in broad regulatory programs, such as transcription activation domains and E3 degron signals 3,22,57,64 . These approaches also exemplify a strategy to understand the effects of sequence variants and mutations in disordered peptides, which have distinct behavior from folded domains and are less suited to structure-guided approaches.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies with yeast PQC degrons have shown that in general an exposed stretch of hydrophobic amino acids without negative charges constitutes a degron ( 20 , 55 , 56 ) and that in mammalian cells similar rules apply ( 14 ). This is in agreement with the notion that hydrophobic amino acids are mostly embedded in the interior of globular proteins ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Negatively charged amino acids might act as stabilizing factors in protein sequences. It has been reported that the use of a negative amino acid at position −1 (exchange Q to E) within a degron sequence leads to substrate stabilization and loss of interaction with the mammalian ubiquitin–protein ligase TRIM7 ( 22 ) as well as that negatively charged amino acids are generally scarce in yeast degrons and counteract degradation signals when placed in the core of a degron ( 55 ). We observed aspartate at all six positions associated with stable variants.…”
Section: Discussionmentioning
confidence: 99%